SOSIALISASI TINGGALAN SRIWIJAYA DI KOTA PALEMBANG BAGI GURU MATA PELAJARAN SEJARAH TINGKAT SMA Se-KOTA PALEMBANG - Pahlevi, Muhammad Reza; Hudaidah, Hudaidah; Yusuf, Syafruddin; Syarifuddin, Syarifuddin (STKIP Persada Khatulistiwa Sintang, 2023)
ABSTRACTThis activity was carried out by the Service Team for the History Education Study Program, FKIP Sriwijaya University in 2022 using the Zoom Meeting application. The urgency behind the implementation of this activity is the lack of optimal learning of local history in high schools in Palembang and its surroundings. The socialization of the preservation of Sriwijaya heritage in the city of Palembang is one of the many local histories found in the province of South Sumatra, precisely in the city of Palembang. So far, teachers have only focused on national history materials contained in government textbooks. In fact, the material in government textbooks is far from the reality and circumstances that surround students. The method used in this activity is the lecture method which is varied with discussion and question and answer, as well as assignments made by participants. This activity can be said to be successfully carried out with indicators of an increase in the understanding of teachers regarding the socialization of the Sriwijaya heritage in Palembang City with an average pre-test score of 40 and an average post-test score of 90. This figure shows a difference of 50 which means there is increasing understanding of the socialization of the remains of Sriwijaya in Palembang City by carrying out community service activities in the form of socializing local history materials.Keywords: Material socialization, Sriwijaya's legacy in Palembang City, Local history learning, History teacher throughout Palembang City.Â ABSTRAKKegiatan ini dilaksanakan oleh Tim Pengabdian Prodi Pendidikan Sejarah FKIP Universitas Sriwijaya tahun 2022 dengan menggunakan aplikasi zoom meeting. Adapun urgensi yang melatarbelakangi dilaksanakannya kegiatan ini adalah kurang optimalnya pembelajaran sejarah lokal di SMA yang ada di Palembang dan sekitarnya. Sosialisi pelestarian peninggalan Sriwijaya Di kota Palembang merupakan salah satu dari sekian banyak sejarah lokal yang terdapat di Provinsi Sumatera Selatan, tepatnya di Kota Palembang. Selama ini para guru hanya berfokus pada materi sejarah nasional yang terdapat di dalam buku teks pemerintah. Padahal, materi yang ada di dalam buku-buku teks pemerintah jauh dari realitas dan keadaan yang ada di sekitar peserta didik. Metode yang digunakan dalam kegiatan ini adalah metode ceramah yang divariasikan dengan diskusi dan tanya-jawab, serta penugasan yang dilakukan oleh peserta. Kegiatan ini dapat dikatakan berhasil dilaksanakan dengan indikator terjadinya peningkatan pemahaman para guru mengenai sosialisasi tinggalan Sriwijaya di Kota Palembang dengan skor rata-rata pre-test sebesar 40 dan skor rata-rata post-test sebesar 90. Angka tersebut menunjukkan selisih sebesar 50 yang berarti terdapat peningkatan pemahaman terhadap sosialisasi tinggalan Sriwijaya di Kota Palembang dengan dilakukannya kegiatan pengabdian pada masyarakat dalam bentuk sosialisasi materi sejarah lokal.Kata Kunci: Sosialisasi materi, Tinggalan Sriwijaya di Kota Palembang, Pembelajaran sejarah lokal, Guru sejarah se-Kota Palembang.